If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying sqrt(2x + -5) + sqrt(4x + -7) = 2 Reorder the terms: qrst(-5 + 2x) + sqrt(4x + -7) = 2 (-5 * qrst + 2x * qrst) + sqrt(4x + -7) = 2 (-5qrst + 2qrstx) + sqrt(4x + -7) = 2 Reorder the terms: -5qrst + 2qrstx + qrst(-7 + 4x) = 2 -5qrst + 2qrstx + (-7 * qrst + 4x * qrst) = 2 -5qrst + 2qrstx + (-7qrst + 4qrstx) = 2 Reorder the terms: -5qrst + -7qrst + 2qrstx + 4qrstx = 2 Combine like terms: -5qrst + -7qrst = -12qrst -12qrst + 2qrstx + 4qrstx = 2 Combine like terms: 2qrstx + 4qrstx = 6qrstx -12qrst + 6qrstx = 2 Solving -12qrst + 6qrstx = 2 Solving for variable 'q'. Move all terms containing q to the left, all other terms to the right. Reorder the terms: -2 + -12qrst + 6qrstx = 2 + -2 Combine like terms: 2 + -2 = 0 -2 + -12qrst + 6qrstx = 0 Factor out the Greatest Common Factor (GCF), '2'. 2(-1 + -6qrst + 3qrstx) = 0 Ignore the factor 2.Subproblem 1
Set the factor '(-1 + -6qrst + 3qrstx)' equal to zero and attempt to solve: Simplifying -1 + -6qrst + 3qrstx = 0 Solving -1 + -6qrst + 3qrstx = 0 Move all terms containing q to the left, all other terms to the right. Add '1' to each side of the equation. -1 + -6qrst + 1 + 3qrstx = 0 + 1 Reorder the terms: -1 + 1 + -6qrst + 3qrstx = 0 + 1 Combine like terms: -1 + 1 = 0 0 + -6qrst + 3qrstx = 0 + 1 -6qrst + 3qrstx = 0 + 1 Combine like terms: 0 + 1 = 1 -6qrst + 3qrstx = 1 The solution to this equation could not be determined. This subproblem is being ignored because a solution could not be determined. The solution to this equation could not be determined.
| 32x+6=31x+2 | | x(-7)(-10)=35 | | -9(x)=3 | | G=-0.100950783B+-0.2972595078*(-0.3396048918B+-3.36406397G+4.703668862Y)+1.398210291Y | | -0.0722B=0.7152G-Y+0.2126R | | -0.7152G=0.0722B-Y+0.2126R | | -0.2126R=0.7152G+0.0722B-Y | | Y=0.2126R+0.7152G+0.0722B | | y=10-0.667*(15-1.5y-2.5z)-1.667z | | 30=2A+3B+5C | | -12.5+5=x | | w^2+16w^2=c | | 10=2A+3B+5C | | 37x=56+89 | | 54x+18x-12-8x=100 | | 34-5x=7-8x | | 6=2x+20 | | 10x-20=9x+9 | | 24x=72*72-48*48 | | 60x=53*53-37*37 | | 12x=34*34-26*26 | | 23x=68*68-45*45 | | 2x+18=45 | | 12x=50*50-38*38 | | (3a+b)2= | | 6cn-2cn= | | 4x+18x+32=54 | | -2y=1-4x | | 3x=1-4y | | (3x-8)(6x^2-14)=0 | | 6x-9=2m+47 | | 27.8x=2880 |